Culture and Freedom of Religion: Interrogating Animal Rights - Chris O. Abakare (Universitas Negeri Makassar, 2021)
When religious freedom and animal interests do clash many people believes that humans have a strong interest being free to practise their religion. Hence, this work interrogates the problem of animals rights within culture and freedom of religious expression. This work evaluated whether the human interest in freedom of religion trumps animals’ interests in avoiding pain and in being killed. This acknowledges that only some few religions actually require their followers to harm animals. Thus, the animal rights advocacy of this work only has the potential to impinge upon religious freedom on a very rare number of occasions. However, for those religious pratices that encourages harming of animals, this work argues that the interest in religion cannot be regarded as ‘special’, meriting priority over any other competing interest. Nor can the goal of equalising individuals’ opportunity to pursue their conception of the good take priority over all other claims. Just as we would not let humans suffer intolerably in the name of religion or equal opportunity, nor should we let animals. And just as we would not let human infants be killed in the name of religion or equal opportunity, nor should we let animals.